1988
DOI: 10.3168/jds.s0022-0302(88)79758-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Relationship Between Linear Functional Type Traits and Milk Yield for Five Breeds

Abstract: Lactation records of cows first calving between 18 and 35 mo were combined with linear type ratings assigned during the same lactation if before 43 mo. Phenotypic relationships were examined between final score and 13 type appraisal traits and first lactation milk yield from 2935 Ayrshire, 3154 Brown Swiss, 13,110 Guernsey, 50,422 Jersey, and 924 Milking Shorthorn records. Most phenotypic correlations between type and milk yield were low. Linear correlations of final score with first lactation milk yield were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
6

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
5
21
1
6
Order By: Relevance
“…As in other studies there was a relationship between udder traits, largest between udder width and rear udder height (0.686). However, the magnitude of genetic correlations obtained in our study, smaller than reported by Lawstuen et al (1987), Norman et al (1988) and Foster et al (1989), might suggest some differences in the scoring system. An examination of the phenotypic and genetic correlations does not indicate that linearly scored traits could be effectively represented by a smaller number of traits.…”
Section: Discussioncontrasting
confidence: 52%
“…As in other studies there was a relationship between udder traits, largest between udder width and rear udder height (0.686). However, the magnitude of genetic correlations obtained in our study, smaller than reported by Lawstuen et al (1987), Norman et al (1988) and Foster et al (1989), might suggest some differences in the scoring system. An examination of the phenotypic and genetic correlations does not indicate that linearly scored traits could be effectively represented by a smaller number of traits.…”
Section: Discussioncontrasting
confidence: 52%
“…Entretanto, valores de correlações genéti-cas negativas, porém menores, também foram encontrados por outros autores, como SYRSTAD (1966), MORRIS e WILTON (1976), NORMAN et al (1988) e KAWAHARA et al (1996).…”
Section: Resultsunclassified
“…NORMAN et al (1988) observaram correlações genéticas negativas e pequenas entre algumas características de tamanho corporal e produção de leite na primeira lactação de vacas Guernsey e Jersey; entretanto, SHORT e LAWLOR (1992) verificaram correlações positivas, porém pequenas, entre características de tamanho e produção de leite em vacas Holandesas. KLASSEN et al (1992) estudaram correlações genéticas entre várias características de tipo e características de produção em vacas Holandesas, encontrando correlações baixas entre característi-cas de tamanho e tempo de vida produtiva.…”
Section: Rev Bras Zootec 29(1):153-158 2000unclassified
“…As correlações fenotípicas entre comprimento, diâmetro e distância das tetas com a altura do úbere foram todas negativas, sugerindo que tetas mais longas e mais calibrosas tenderam para úberes mais próximos do solo, concordando com os resultados encontrados por HIGGINS et al (1980). NORMAN et al (1988) analisaram as relações entre várias características lineares de tipo e a produção de leite à primeira lactação em cinco raças leiteiras, Ayrshire, Brown Swiss, Guernsey, Jersey e Shorthorn, nos Estados Unidos. De todas as características funcionais para tipo, o caráter leiteiro foi o que apresentou a mais alta correlação fenotípica com produção de leite, em todas as raças estudadas (0,19 a 0,53), exceto na Ayrshire, em que a profundidade de úbere (-0,26) e a largura de úbere posterior (0,21) foram superiores.…”
Section: Introductionunclassified